2012
DOI: 10.3390/ijms13067854
|View full text |Cite
|
Sign up to set email alerts
|

Diffusivity Maximum in a Reentrant Nematic Phase

Abstract: We report molecular dynamics simulations of confined liquid crystals using the Gay–Berne–Kihara model. Upon isobaric cooling, the standard sequence of isotropic–nematic–smectic A phase transitions is found. Upon further cooling a reentrant nematic phase occurs. We investigate the temperature dependence of the self-diffusion coefficient of the fluid in the nematic, smectic and reentrant nematic phases. We find a maximum in diffusivity upon isobaric cooling. Diffusion increases dramatically in the reentrant phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The simulations are performed for up to N = 30 000 molecules using the Gay-Berne-Kihara potential [24], which models the liquid crystal molecules as spherocylindrical soft particles possessing anistropic interactions. The potential is known [25,26] to generate a smectic-A phase for appropriate parameter settings. The simulation protocol is described in the Supplemental Material [27].…”
Section: -2mentioning
confidence: 99%
“…The simulations are performed for up to N = 30 000 molecules using the Gay-Berne-Kihara potential [24], which models the liquid crystal molecules as spherocylindrical soft particles possessing anistropic interactions. The potential is known [25,26] to generate a smectic-A phase for appropriate parameter settings. The simulation protocol is described in the Supplemental Material [27].…”
Section: -2mentioning
confidence: 99%
“…Three-dimensional periodic boundary conditions are often used in such simulations to represent a bulk state, but they sometimes induce serious artifacts in chiral phases due to inappropriate periodic images, unless the box length along the twisted axis is an integer of half the pitch distance. In this work, therefore, we used solid substrates with planar anchoring [ 38 , 60 , 61 ] along the axis of helical rotation in order to break symmetry and eliminate boundary artifacts in that axis. The fluid-substrate potential energy is expressed as where is the depth of the attractive well and is the perpendicular distance between molecule i and the lower substrate.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Goto et al showed increase of charge mobility in the nematic phase of LCs [7,8]. Recently, other computer simulation studies revealed that nonpolar LCs, exhibiting a reentrant nematic (RN) phase, can show enhanced rates of translational mobility [9][10][11][12]. This finding was attributed to the lowering of the rotational configurational entropy upon forming a denser RN phase.…”
mentioning
confidence: 98%